The Clash of Corporate Cultures. During the Process of Mergers and Acquisitions - Osieka Bartłomiej (My University, 2004)
This work focuses on the general idea of the organizational culture, inter-organizational change and development. It investigates not only the process of adopting internal cultures of subsidiaries to the major organizational scheme, but also any possible influence of the departments’ cultures on the main unit. The central idea of this thesis is to investigate the characteristics of the organizational cultures of Company A and its subsidiaries. It also explains the process of changes that has influenced all the units. It is crucial to mention that this study is limited only to the idea of corporate culture, thus other changes which not connected to the topic of the research, are not taken into consideration. Thus, the first chapter focus mainly on the theory of organizational culture, where several possible approaches to the described phenomenon are presented. This chapter presents the main research that has been done in the field, including the works of Geert Hofstede (1984, 1997), Edgar H. Schein (1992), Peters and Waterman (1982), Cameron and Freeman (1991), Hampden-Turner and Trompenaars (1993) and many others. The next chapter discusses the theory of the organizational change with the great focus on the change of organizational culture. The section includes the simple model of organizational change and the ethical perspective on organizational change. The chapter also presents the theory of inter-organizational development with a great focus on the idea of mergers and acquisitions. It includes the general theory of inter-organizational alliances and a broader perspective on the idea of mergers and acquisitions including: the definition, history, types and various models of M&A transactions. The third section contains information about the investigated company. It includes the history of the company and the branches, describes the merging process and indicates the implications of the process. The last chapter presents the results of the research that was conducted in the Company A. The research was conducted in the headquarters and the southern branch. It is based on the qualitative research that is followed by several interviews and research of the internal publications. It describes the history and the present situation of the examined company and its subsidiaries, the merging process and the analysis of the organizational culture. It presents the main characteristics of the organizational culture, a comparative cultural analysis of the departments and a future prognosis. To conclude, this thesis is divided into two separate parts: the first is purely theoretical concerning the approaches to the idea of organizational culture, and the second focuses on the qualitative study conducted in the Company A and its branches. Taking into consideration all the idea of organizational cultures and inter-organizational development, it is proposed that the culture of the dominant unit determines the direction of the development of the dependent subsidiaries’ cultures.
Keywords: corporate cultures; mergers; acquisitions; organizational culture; organizational change